Islamic Guided Imagery for Reducing Postpartum Fatigue and Anxiety: Development of Midwifery Care - Azizah, Nurul; Rosyidah, Rafhani; Jayanti, Ratna Dwi (Universitas Tribhuwana Tunggadewi, 2026)
The high incidence of postpartum fatigue and anxiety in Indonesia hindering mothers’ recovery and breastfeeding success. Non-pharmacological and safe interventions aligned with local cultural values are needed. Islamic guided imagery provides relaxation that integrates positive visualization with the spiritual value of zikr. This study aims to examine the effectiveness of Islamic guided imagery in reducing fatigue and anxiety scores in postpartum mothers. The study used a quasi-experimental design with a pre-posttest and a control group. A total of 45 postpartum mothers (0–6 weeks) were recruited using consecutive sampling techniques and divided into intervention (n = 23) and control (n = 22) groups. The Islamic guided imagery intervention was delivered in audio format for 15–20 minutes per day for 3 days, demonstrating its simplicity and feasibility for busy postpartum care routines. Fatigue levels were measured using the Postpartum Fatigue Scale (PFS), and anxiety was measured using the State Anxiety Inventory (STAI-S). Data were analyzed using an independent t-test. The intervention group showed a significant and progressive reduction in fatigue and anxiety scores from day 1 to day 3 compared with the control group (p 0.001). The quick improvements of -15.8 and -17.7 points in fatigue and anxiety scores, respectively, can inspire healthcare providers and researchers to consider this intervention as an effective, fast-acting option. The Islamic guided imagery effectively reduces postpartum fatigue and anxiety by strengthening emotional regulation and spiritual coping. Recommendations for future research include conducting randomized controlled trials with longer follow-up and including stress biomarker measurements to strengthen the generalizability of findings.